International gross capital flows: A new measure and application to a global panel - Thorsten Janus; Daniel Riera-Crichton (University of California, Santa Cruz Institute for International Economics (SCIIE), 2009)
This paper presents a new measure of international gross capital flows and applies it to a global panel from 1970 to 2004. We explain why paying attention to the gross flows underlying net capital flows may be important and how our gross flow measure differs from the standard measure in the literature. For example, while by the standard measure a capital inflow decline more than fully explains Mexico's current account reversal during the 1994-95 Tequila Crisis, our measure assigns an important role to capital outflows and implies a 63 percent higher outflow in 1995 compared to the standard measure outflow.
Keywords: F21; F32; F36; G15; 330; gross international capital flows; balance of payments; financial openness; current account imbalances; financial crises; Kapitalmobilität; Zahlungsbilanzungleichgewicht; Messung; Mexiko